The Effect of Candesartan Alone and Its Combination With Estrogen on Post-traumatic Brain Injury Outcomes in Female Rats - Hajmohammadi, Mojdeh; Khaksari, Mohammad; Soltani, Zahra; Shahrokhi, Nader; Najafipour, Hamid; Abbasi, Reza (Frontiers in Neuroscience, 2019)
Aim: The aim of this study was to evaluate the effect of ineffective single doses of candesartan (angiotensin II type I receptor blocker) on blood pressure alone and its combination with estrogen on the changes in brain edema, the intracranial pressure (ICP) and cerebral perfusion pressure (CPP) following diffuse traumatic brain injury (TBI) in female rats. Methods: TBI was induced in ovariectomized female rats using Marmarou's method. The treatment groups received low dose (LC) and high dose (HC) of candesartan, estrogen (E2), a combination of estrogen with low dose (E2 + LC) and high dose of candesartan (E2 + HC). ICP and CPP were measured before and several times after TBI, and the brain water content (brain edema) was measured 24 hours after the TBI. Results: After the TBI, brain edema and ICP in estrogen group was lower than that of vehicle and TBI groups. Brain edema and ICP in HC group declined compared to vehicle group after TBI. Significant differences in ICP and brain edema were observed between E2 + HC and E2 + LC groups with Oil + vehicle group after TBI. Significant increase in CPP was shown in estrogen group 4 and 24 hours post TBI, while in HC and E2 + LC groups, 24 hours. Conclusions: Candesartan caused beneficial changes in TBI consequences; whereas, combination of estrogen with candesartan did not show any additive or synergistic effect. However, the effect emerged for low dose of candesartan suggests interaction between low dose of candesartan and estrogen.